2017
DOI: 10.13044/j.sdewes.d5.0149
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Adaptation and Flood Management in Metro Vancouver Regional Area: Can an Exercise in Herding Cats be Successful?

Abstract: Climate change poses novel challenges for cities, threatening long-term sustainability objectives and necessitating investments in resilience. Climate change exacerbates the challenge of identifying the range of impacts of natural hazards in terms of scale and frequency. This study focuses on climate change adaptation responses with regard to flood management in the Metro Vancouver regional area, which is the last large non-amalgamated region in Canada. It is comprised of 24 local authorities and a regional go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Further adaptation examples can be found in urban areas near the Fraser River floodplain, an area that is highly vulnerable to sea level rise due to low-lying geology and dense population (Yumagulova and Vertinsky 2017). A recent analysis found that the costs of sea level related damage to on-shore built infrastructure would be higher in coastal BC than any other coastal region in Canada (Withey et al 2016).…”
Section: Communities and Marine Infrastructurementioning
confidence: 99%
“…Further adaptation examples can be found in urban areas near the Fraser River floodplain, an area that is highly vulnerable to sea level rise due to low-lying geology and dense population (Yumagulova and Vertinsky 2017). A recent analysis found that the costs of sea level related damage to on-shore built infrastructure would be higher in coastal BC than any other coastal region in Canada (Withey et al 2016).…”
Section: Communities and Marine Infrastructurementioning
confidence: 99%
“…This allowed for collaborative efforts to take place in order to support a specific targeted adaptation agenda in the City of Vancouver and the region broadly. Yumagulova and Vertinsky (2017) characterize this approach as a reactive strategy and suggest that the majority of such structural developments have been motivated by the damage caused by devastating flood events like the 1948 Fraser flood. This response was also prompted by other factors including a lack of federal and provincial responsibility regarding hazard mitigation, inadequate floodplain mapping, in addition to insufficient oversight of municipal land use policies by higher levels of government (Yumagulova & Vertinsky, 2017).…”
Section: Shifting Responsibility For Flood Risk Reductionmentioning
confidence: 99%
“…Yumagulova and Vertinsky (2017) characterize this approach as a reactive strategy and suggest that the majority of such structural developments have been motivated by the damage caused by devastating flood events like the 1948 Fraser flood. This response was also prompted by other factors including a lack of federal and provincial responsibility regarding hazard mitigation, inadequate floodplain mapping, in addition to insufficient oversight of municipal land use policies by higher levels of government (Yumagulova & Vertinsky, 2017). Furthermore, The Canada Water Conservation Assistance Act in place from 1953 to 1970 allowed senior levels of government to provide grants to municipalities covering up to 75 percent of the cost required to construct structural defense infrastructure (Shrubsole, 2007).…”
Section: Shifting Responsibility For Flood Risk Reductionmentioning
confidence: 99%
“…Notably, rooftops can be a good alternative for increasing green spaces in cities where additional space is difficult to secure owing to high land prices and various conflicts of interest [9,10]. As a result, several studies [11][12][13][14] were conducted to effectively create rooftop greening and roadside trees in cities. Meyer [11] proposed a conceptual description of the individual effects of trees and offers a guideline for tree planting to increase such effects.…”
Section: Introductionmentioning
confidence: 99%